A review of the preparation, properties and applications of VO2 thin films with the reversible phase transition - Wen, Chong; Feng, Liquan; Li, Zhaohui; Bai, Jinglian; Wang, Shaoyan; Gao, Xingxing; Wang, Jian; Yao, Wenqing (Frontiers in Materials, 2024)
The reversible phase transition of vanadium dioxide under thermal, electrical, and optical stimuli is the enabling concept for the functioning of smart materials and is the basis for the development of various device materials such as optical, electrical, thermal, and mechanical devices based on VO2 on rigid and flexible platforms. The phase transition temperature of VO2 near room temperature is considered an excellent choice and a potential candidate to replace traditional materials in a variety of applications. There is a growing interest in VO2 applications for a wide range of devices, and the use of VO2's structure to manipulate and explore the functions of various application devices, as well as the modification of VO2 structures to improve performance in a variety of materials, can lead to extremely exciting innovations. A lot of effort has been put into the challenges of practical production and practical application, and it is necessary to find an industrially feasible manufacturing method for the preparation of VO2 films, which is the basis for the practical application of VO2based equipment. Based on this background, we first briefly describe the structure of VO2, the phase transition mechanisms involved, and the factors and other properties induced by the phase transition of VO2. Then, the current status and advantages and disadvantages of VO2 thin film preparation technologies are introduced in detail, including pulsed laser deposition (PLD), magnetron sputtering, the sol-gel method, and chemical vapour deposition (CVD). In addition, we propose three strategies to improve the performance of VO2 thin films, including element doping, multi-layer composites, and surface structure. We also discussed the different applications of VO2 under thermal, electrical, and light stimulation, as well as the development trends and future challenges of VO2 thin films.